MHD boundary layer flow of Casson fluid under the influences of radiation on mass transfer and exponentially stretching sheet with heat sink / Muhammad Afiq Sahasdi - Sahasdi, Muhammad Afiq (2017)
Casson fluid which is characterised by the non-Newtonians fluid behaviour is applicable in various industrial processes which include polymer and metal extrusion, wire drawing and paper production process. In this study, MHD boundary layer flow of Casson fluid over an exponentially stretching sheet with heat sink is anylysed. The study is an extrusion of the work done by Devi et al. (2014) and Pramanik (2014). It involves modification of the momentum equation is the system of partial differential equation. The governing system of partial differential equation is the transformed into a system of ordinary differential equations. The system of ordinary differential equation is then solved numerically using the Runge-Kutta-Fehlberg method in using MAPLE 15 environment. The numerical results of momentum, temperature and concentration profiles are presented graphically for various parameters such as magnetic parameter M, heat sink parameter Q, radiation parameter R, Schmidt number Sc, Prandtl number Pr and Casson parameter ft. The numerical values for skin friction coefficient, local Nusselt number and local Sherwood number are tabulated and discussed. It is found that as the magnetic and Casson parameter are increased, the temperature and concentration profiles also increased. It is also found that an increase in radiation parameter and heat sink parameter result an increase in thermal boundary layer thickness.